Pelatihan Manajemen Nyeri Non Farmakologis pada Kader Kesehatan di Posyandu Bergas Waras - Wirakhmi, Ikit Netra; Ningrum, Ema Wahyu; Rahmawati, Arni Nur (Universitas Pahlawan Tuanku Tambusai, 2026)
Pain is one of the most common complaints experienced by people across various age groups. Unfortunately, pain management is still largely dominated by the use of medications, while safer and simpler non-pharmacological approaches that can be implemented at the family level remain poorly known and underutilized. Posyandu cadres, as the frontline of primary healthcare services, have great potential to educate communities; however, their knowledge of non-pharmacological pain management techniques is still limited. Therefore, this training program is essential to strengthen the cadres’ capacity in helping communities manage pain independently and holistically. This community service activity aims to improve the cadres’ attitudes and self-efficacy toward non-pharmacological pain management. The activities included education on non-pharmacological pain management and hands-on practice. In addition, pre- and post-tests were conducted to measure attitudes and self-efficacy.